FROM BLUE JEANS TO BLUE GENES - Boon, Laurence M. (2009)
Cutaneous venous anomalies are common. They are blue in color and vary in size, number and location, and account for the majority of consultations at specialized interdisciplinary clinics for vascular anomalies. Venous lesions are clinically important as they cause pain, dysfunction, destruction of adjacent tissues and esthetic concern. Only resection and sclerotherapy are helpful, although not always curative. Understanding etiopathogenesis could help design animal models and develop novel therapeutic approaches. Dr Mulliken envisioned a project to uncover the genetic basis of an inherited form of venous malformation in a large New England family. Recruitment of two young fellows resulted in a collaborative project that unraveled the searched-for-gene and its mutation. This was an opening for a new era in the field of vascular anomalies. Two blue genes’ mutations were discovered, which account for the majority, if not all, of the inherited forms of venous anomalies, but other genes as well, for rheologically diverse lesions. Differential diagnosis and management has improved, and animal models are being made. This was achieved thanks to Dr Mulliken, who inspired two young investigators in blue jeans to find two blue genes.